Implementasi Prinsip Ibadah dalam Islam oleh Muhammadiyah: Hubungan Akhlak dan Moralitas Masyarakat - Riska Amaliah; Fahria Musa'ad; Andi Hikmayani Makmur; Abbas Baco Miro; Ahmad Nashir (CV. ITTC INDONESIA, 2026)
This study examines the concept of worship from the perspective of Muhammadiyah, which emphasizes the importance of worship not only as a ritual but also as a means of character and moral formation. This study uses a qualitative approach with a case study method, involving interviews with Muhammadiyah members. The results show that Muhammadiyah views worship as an educational process that shapes ways of thinking, behaving, and acting in personal and social life. This organization emphasizes the importance of understanding and practicing Islamic teachings based on the Quran and Sunnah, and encourages its members to be open, responsible, and critical in their worship. This study also highlights the challenges Muhammadiyah faces in actualizing the principles of worship in the current era of social change.